2016
DOI: 10.1038/nrrheum.2016.112
|View full text |Cite
|
Sign up to set email alerts
|

Affective disturbance in rheumatoid arthritis: psychological and disease-related pathways

Abstract: In addition to recurrent pain, fatigue, and increased rates of physical disability, individuals with rheumatoid arthritis (RA) show an increased prevalence of some mental health disorders, particularly those involving mood disturbances. This narrative Review provides an overview of mental health comorbidities in RA, and discusses how these comorbidities interact with disease processes, including dysregulation of inflammatory responses, prolonged difficulties with pain and fatigue, and the development of cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
173
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 172 publications
(191 citation statements)
references
References 139 publications
(181 reference statements)
11
173
1
6
Order By: Relevance
“…Some evidence in rheumatic diseases, which corresponds with evidence from other chronic illnesses, has also indicated that specific ways of regulating emotions, including difficulty in identifying and describing emotions (alexithymia) and emotional suppression, are predictive of impaired quality of life and increased self-reported disease activity, whereas other strategies, such as emotional expression, could be associated with improved functioning under specific circumstances [41,50e52]. Acceptance and self-efficacy have been shown to generally protect against psychological distress and increase in physical symptoms [2,8,23]. More recently, the role of expectancies has become a research topic of particular interest in the area of placebo effects, in which expectancies, for example, with regard to treatment effectiveness, have been shown to be a strong predictor of subsequent outcomes including pain.…”
Section: Prospective Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Some evidence in rheumatic diseases, which corresponds with evidence from other chronic illnesses, has also indicated that specific ways of regulating emotions, including difficulty in identifying and describing emotions (alexithymia) and emotional suppression, are predictive of impaired quality of life and increased self-reported disease activity, whereas other strategies, such as emotional expression, could be associated with improved functioning under specific circumstances [41,50e52]. Acceptance and self-efficacy have been shown to generally protect against psychological distress and increase in physical symptoms [2,8,23]. More recently, the role of expectancies has become a research topic of particular interest in the area of placebo effects, in which expectancies, for example, with regard to treatment effectiveness, have been shown to be a strong predictor of subsequent outcomes including pain.…”
Section: Prospective Studiesmentioning
confidence: 99%
“…Regarding the social aspects within the healthcare context, a satisfactory relationship between the care provider and patient, which, for example, consists of mutual trust and active participation of the patient in treatment and decision making, has been shown to be an important predictor of high patient engagement and well-being in inflammatory rheumatic diseases. High patient engagement or empowerment has been shown to be related to improved treatment adherence, treatment satisfaction, and health-related quality of life [2].…”
Section: Prospective Studiesmentioning
confidence: 99%
See 3 more Smart Citations